Module Design of Self-reconfigurable Modular Robot: A Survey - DAI Ye; ZHANG Qi-hao; GAO Yu-fei; Qi Yun-shan; WANG Jian-hui (Journal of Harbin University of Science and Technology, 2021)
Self-reconfigurable modular robot is a robot assembled through one or more modules and can be reconstI11cted into another configuration according to the changes of working environment. It has the advantages of wide control range, variable structure, simple function and easy expansion. Self-reconfigurable modular robot has become a reseach hotspot in academic and industrial fields. In order to discuss the rese打ch progress of modular design of self-reconfigurable modulrobots in recent years, the modular suctures of representative achievements at home and abroad are sorted out, and the self-reconfigurable modular robots are classified from two aspects: isomorphism and heterogeneity, series and array. On this basis, the main problems existing in the research are analyzed. The possible development direction is put fo1-wai·d and the future research is prospected.